THE IMPACT OF NITROGEN FERTILIZATION IN ALKALOID CONTENT AND GROWTH TRAITS OF DATURA STRAMONIUM L. - KIZIL, Suleyman; TONCER, Ozlem; SOGUT, Tahsin (Journal of Agricultural Sciences (Belgrade), 2024)
D. stramonium is a wild plant species belonging to the Solanaceae family and grows on the edges of cotton fields, empty lands and roadsides. The plant is a most important medicinal plant which has both toxics and medicinal properties. It contains a variety of toxic tropane alkaloids such as atropine, hyoscamine, and scopolamine. It is known that cultivation techniques have a great influence on the quality and quantity of secondary metabolites. For this reason, it is important to determine the optimal values of agronomic factors that affect plant growth and production. This study was conducted in Dicle University Agricultural Faculty Experimental area in 2010-2011 years.The purpose of the present study was to evaluate the impact of nitrogen fertilizers (0, 50, 100 and 200 kg ha-1) on some agronomical characteristics such as fresh & drug herb yield and total alkaloid content of datura (Datura stramonium L.). Significant differences were observed between nitrogen doses according to two years mean in seed yield, fresh & dry herb yield and total alkaloid yield of seed. Seed yield were changed between 545 kg ha-1 and 625 kg ha-1, fresh herb yield between 8000 and 24483 kg ha-1, dry herb yield between 2190 kg ha-1 and 5083 kg ha-1 and alkaloid content between 0.259% and 0.366%, respectively. The results showed that fresh and dry herb yields were increased with increasing nitrogen doses.